Invited presentation: Versatile diamond nanosensor devices - Nelz, Richard; Opaluch, Oliver; Hochstetter, Axel; Rani, Dipti; Oshnik, Nimba; Neu, Elke (Optics InfoBase Conference Papers, 2020)
We present novel fabrication techniques for single crystal diamond nanostructures containing shallow nitrogen vacancy color centers and their scalability. We demonstrate near-field energy transfer between NV centers and 2D materials and multi-functional sensing capabilities of NV centers.
CRIS-Team Scopus Importer:2023-03-27